Functional recapitulation of transitions in sexual systems by homeosis during the evolution of dioecy in Thalictrum - LaRue, Nicole C.; Sullivan, Alessandra M.; Di Stilio, Verónica S. (Frontiers in Plant Science, 2013)
Sexual systems are highly variable in flowering plants and an important contributor floral diversity. The ranunculid genus Thalictrum is especially well suited to study evolutionary transitions in sexual systems. Homeotic transformation of sexual organs (stamens and carpels) is a plausible mechanism for the transition from hermaphroditic to unisexual flowers in this lineage because flowers of dioecious species develop unisexually from inception. The single-copy gene PISTILLATA (PI), constitutes a likely candidate for rapid switches between stamen and carpel identity. Here, we first characterized the expression pattern of all B class genes in the dioecious species T. dioicum. As expected, all B class orthologs are expressed in stamens from the earliest stages. Certain AP3 lineages were also expressed late in sepal development. We then tested whether orthologs of PI could potentially control sexual system transitions in Thalictrum, by knocking-down their expression in T. dioicum and the hermaphroditic species T. thalictroides. In T. dioicum, we found that ThdPI-1/2 silencing caused stamen primordia to develop into carpels, resulting in male to female flower conversions. In T. thalictroides, we found that ThtPI silencing caused stamen primordia to develop into supernumerary carpels, resulting in hermaphroditic to female flower conversions. These phenotypes illustrate the ability for homeotic mutations to bring about sudden and potentially adaptive changes by altering the function of a single gene. We propose a two-step evolutionary model where transitions from hermaphroditic to unisexual plants in Thalictrum result from two independent mutations at a B class gene locus. Our PI knockdown experiments in T. thalictroides recapitulate the second step in this model: the evolution of female plants as a result of a loss-of-function mutation in a B class gene.